Biofortificação agronômica com zinco em cultivares de alface crespa - Graciano, Patricia Diniz (2019)
Lettuce (Lactuca sativa L.) is a leafy vegetable of great importance in food and human health, especially as a source of vitamins and minerals. In underdeveloped countries, deficiencies of iron, zinc and vitamin A are a public health problem. Despite the importance of these elements in human health, the main foods consumed in developing countries have low levels, making their consumption insufficient to meet the minimum daily requirements. The objective of this study was to evaluate the effect of different doses of zinc via leaf on four cultivars of crisp lettuce. The experiment was a field research, which occurred in Federal University of Uberlandia - Monte Carmelo Campus. The trial design was a randomized complete block design in a 4x5 factorial scheme with four replicates, four cultivars of crisp lettuce (Brida, Isabela, Thaís, Vanda) and five doses of zinc sulphate per leaf (0, 400, 800, 1200 and 1600 g ha-1 of zinc). When the plants were fully developed, it was evaluated: SPAD index, plant height (cm), total fresh mass (kg plant-1), stem diameter (mm), head diameter (cm), number of leaves per plant, estimated average productivity (kg m- 2) and zinc foliar content. Data were submitted to analysis of variance by the F test (α = 0.05). For the qualitative data, the averages were compared by the Tukey test at 5% probability and for the quantitative data, regression analyzes were performed. There was a significant interaction between cultivars and Zn doses at the 5% probability level for plant height, total fresh mass, SPAD index and average productivity. According to the results obtained, it was concluded that all evaluated lettuce cultivars can be considered biofortified, but the cultivar Thaís stands out because it has a high content of leaf zinc and satisfactory results for most of the evaluated agronomic characteristics. The doses of 300 to 706 g ha-1 of foliar zinc can be used to be applied in the lettuce crop, because they provide biofortified plants, without affecting the great majority of the productive characteristics of the crop.